Letter to the Editor - anonymous (Management Science, 1959)
I should like to take exception with Mr. Melvin L. Greenhut's statement that “both Weinwurm and Flood are correct” (“Mathematics, Realism and Management Science” by Melvin L. Greenhut, Management Science, April 1958, p. 315). There is no intention to reopen the discussion about the merits or demerits of our individual position; I merely wish to keep the record straight.